Effect of consumption of millets on prevalence and severity of anaemia during pregnancy - Sharma, Nishal; Kishore, Jugal; Gupta, Monika; Singla, Himal; Dayma, Rohini; Sharma, J. B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Anaemia is the commonest medical disorder in pregnancy. Methods: A cross-sectional study was performed on 430 pregnant women in second and third trimester of pregnancy to know the effect of consumption of millets on prevalence of anaemia. Results: A total of 42 (9.77%) women (group one) consumed millets in pregnancy while 388 (90.33%) didn’t consume millets (group 2). Mean age, parity, body mass index (BMI), and gestation were 26.4±4.3 years, 1.9±0.8, 22.6±2.6 kg/m2 and 29.3±2.8 weeks in group 1 and 26.8±4.4 years, 2.1±0.9, 23.1±2.7 kg/m2 and 28.2±2.7 weeks in group 2 respectively, and were similar. Patients education, occupation and mean family income were similar in two groups. Out of 42 patients consuming millets in pregnancy, pearl millet, sorghum, finger millet and barley were consumed by 47.62%, 11.90%, 14.28% and 14.28% patients respectively. Mean calories were equal in the two groups, but mean proteins and iron were significantly higher in group 1 than in group 2 (61.28±6.2 gm and 31.4±3.42 mg versus 56.75±5.7 gm and 22.5±2.51 mg). The prevalence of anaemia was significantly less (40.48%) in group 1 (millets group) than in group 2 (49.74%) (p=0.04). Mild, moderate, and severe anaemia were all less common in the millets group than in non-millet group. Conclusions: The prevalence of anaemia in pregnancy was significantly less common in women consuming millets. There is need to encourage consumption of millets in pregnancy to reduce prevalence of anaemia in pregnancy.